8-F2-isoprostane, thioredoxin and thioredoxin reductase levels in children with obsessive–compulsive disorder. (3rd October 2018) - Bilgiç, Ayhan; Çolak Sivri, Rukiye; Kılınç, İbrahim
Abstract: Purpose: Accumulating data demonstrate that oxidative stress may play a crucial role in obsessive–compulsive disorder (OCD). This study aimed to investigate the role of 8-F2-isoprostane, thioredoxin (Trx), and thioredoxin reductase (TrxR) in children with OCD. Materials and methods: Thirty-three drug-free children with OCD and 35 healthy controls were included in this study. The severity of OCD symptoms was assessed via the Children's Yale Brown Obsessive-Compulsive Scale. The severity of anxiety levels was determined through the Screen for Child Anxiety-Related Emotional Disorders. Plasma levels of 8-F2-isoprostane, Trx, and TrxR were measured using commercial enzyme-linked immunosorbent assay kits. Results: Plasma 8-F2-isoprostane, Trx, and TrxR levels did not show any significant differences between patient and control groups. There were no significant correlations between plasma levels of these antioxidants and severity of OCD. Conclusions: Findings of this study did not support the involvement of oxidative stress in the etiology of childhood OCD.